HALAL HOTELS IN MALAYSIA: CERTIFICATION, ISSUES AND CHALLENGES - Sabidin, Farhana Binti (THE Journal : Tourism and Hospitality Essentials Journal, 2015)
Malaysia is one of the Muslim countries that identified as a new player in tourism industry. In 2004, Malaysia launched Halal Hub and the MS1500:2004 standard brought Malaysia to be recognized as a Halal Food Hub. Of course, since 911 incident happened last 8 years, Malaysia seems to be one of the favourite’s destinations. The increase number of devoted Muslim tourists whom seek for halal food and beverages lead Malaysia to be involved in the halal hotel industry. Halal food is the main factor why Malaysia able to attract more tourists as the demand of halal food is expected to increase. Tourists think that Malaysia is 100% halal community, but in fact they were wrong. This is due to the failures of some hotel to obtain the halal certification. JAKIM, SIRIM and HDC play a vital role in promoting the halal environment among Malaysian hotels. These three institutions identified as the most important recognized bodies in pursuing the halal efforts. Malaysian hotels should aware the significance of going halal so as to be the global halal food hub in the Muslim world.